Clinical features of acute coronary syndrome associated with spontaneous coronary artery dissection in women: a case series - D. N. Nedbaeva; A. S. Aseeva; E. V. Zhiduleva; E. V. Mineeva; A. N. Yakovlev; G. A. Kukharchik (Российский кардиологический журнал)
Spontaneous coronary artery dissection (SCAD) is defined as a spontaneous dissection of the coronary artery wall that occurs independently of atherosclerosis, percutaneous coronary intervention, or mechanical trauma. Its distinctive feature is high prevalence in young women. This condition is associated with pregnancy and hormonal changes. A number of risk factors have been identified, including vascular pathology (most commonly fibromuscular dysplasia), other hereditary connective tissue disorders, systemic inflammatory diseases, migraine, and thyroid diseases. Nevertheless, the precise mechanisms of the pathophysiological relationship remain to be elucidated, and risk factors cannot be identified in all patients, indicating the complex and incompletely understood nature of the disease. The present article presents a case series on the development of SCAD in women and a review of the predisposing factors for the disease.